Energy-protein supplementation before and after parturition of Nellore primiparous cows in the Brazilian tropical savannah (Research, Society and Development, 2021)
Reproduction is associated to the profitability of beef herds, which affects the level of productivity and is influenced by nutritional level. The objective of this study was to evaluate the effect of protein and energy supplementation, before and after parturition, on reproductive variables of Nellore primiparous cows extensively raised in the Brazilian tropical savannah. Eighty pregnant heifers with parturition estimated for a 45 d period during the dry season were randomly divided into four treatments: Control, received a mineral salt and urea mixture pre and postpartum; PRE, protein-energy mixture from the 210th gestational day until parturition; POS, protein-energy mixture from parturition until 90 d afterwards; PREPOS, protein/energy mixture from the 210th gestational day until the 90th day after parturition. Number of days to complete uterine involution (UI) was 37.0 (Control); 31.3 (PRE); 33.1 (POST) and 25.3 (PREPOST) with differences (P